Peningkatan Literasi Antikorupsi Berbasis Ekonomi Islam bagi Komunitas SSQ Holistik Internasional melalui Webinar Pengabdian Masyarakat: Pengabdian - Rita Zunarti; Rahmawati Akeda; Opik Taupik; Puti Khairani Rijadi; Ahalik Ahalik; Ahmad Zaki Mubarok; Kristanti Rahman; Junet Kaswoto; Kurnia Rusmiyati (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Corruption constitutes a form of behavioral deviation that not only violates positive law and social norms but also fundamentally contradicts the core values of Islamic economics. Within the framework of Islamic economic thought, corruption is understood as a breach of amanah (trust), which results in the erosion of justice, the loss of material and spiritual blessing (barakah), and the disruption of public welfare. This condition underscores the necessity of sustained educational efforts to instill anti-corruption values from an early stage. This Community Service Program (PkM) was implemented in collaboration with SSQ Holistik Internasional as a partner institution, aiming to enhance anti-corruption literacy and awareness through an Islamic economics approach that emphasizes the internalization of Islamic values. The program was conducted in the form of a webinar, encompassing the delivery of conceptual materials, interactive discussions, and collective value reflection among participants. The results indicate an improvement in participants’ understanding of the concepts of amanah, justice, and economic responsibility within the Islamic perspective, as well as increased awareness that corruption entails not only legal consequences but also moral, social, and economic implications. Accordingly, this activity contributes to strengthening spiritually grounded anti-corruption literacy and Islamic economic ethics as a sustainable strategy for corruption prevention.